Pinctada margaritifera responses to temperature and pH: Acclimation capabilities and physiological limits. (5th December 2016) - Le Moullac, Gilles; Soyez, Claude; Latchere, Oihana; Vidal-Dupiol, Jeremie; Fremery, Juliette; Saulnier, Denis; Lo Yat, Alain; Belliard, Corinne; Mazouni-Gaertner, Nabila; Gueguen, Yannick
Abstract: The pearl culture is one of the most lucrative aquacultures worldwide. In many South Pacific areas, it depends on the exploitation of the pearl oyster Pinctada margaritifera and relies entirely on the environmental conditions encountered in the lagoon. In this context, assessing the impact of climatic stressors, such as global warming and ocean acidification, on the functionality of the resource in terms of renewal and exploitation is fundamental. In this study, we experimentally addressed the impact of temperature (22, 26, 30 and 34 °C) and partial pressure of carbon dioxide p CO2 (294, 763 and 2485 μatm) on the biomineralization and metabolic capabilities of pearl oysters. While the energy metabolism was strongly dependent on temperature, results showed its independence from p CO2 levels; no interaction between temperature and p CO2 was revealed. The energy metabolism, ingestion, oxygen consumption and, hence, the scope for growth (SFG) were maximised at 30 °C and dramatically fell at 34 °C. Biomineralization was examined through the expression measurement of nine mantle's genes coding for shell matrix proteins involved in the formation of calcitic prisms and/or nacreous shell structures; significant changes were recorded for four of the nine ( Pmarg -Nacrein A1, Pmarg -MRNP34, Pmarg -Prismalin 14 and Pmarg -Aspein). These changes showed that the maximum and minimum expression of these genes was at 26 and 34 °C, respectively. Surprisingly, the modelled thermal optimum for biomineralization (ranging between 21.5 and 26.5 °C) and somatic growth and reproduction (28.7 °C) appeared to be significantly different. Finally, the responses to high temperatures were contextualised with the Intergovernmental Panel on Climate Change (IPCC) projections, which highlighted that pearl oyster stocks and cultures would be severely threatened in the next decade. Graphical abstract: Under the current temperature regime (black line; dotted line is the confidence interval at 5%), pearl oysters spends 121 days above their thermal optimum (blue line). Under the Representative Concentration Pathway (RCP) scenarios 2.6 (+1 °C), this would be 210 days (yellow), 252 days under the RCP 4.5 (+1.5 °C; orange) and 365 days under the RCP8.5 (+2.5 °C; red). Highlights: At the end of the century, the pearl oyster will be stressed 200 + days a year. High temperatures induce metabolic deficits in the pearl oyster. Optimal temperatures for shell growth and somatic growth are different. Short exposures to low pH levels did not affect the pearl oyster's bioenergetics.